DEEP DIALOGUE / CRITICAL THINKING (KONSEP SOLUSI PEMBELAJARAN INOVATIF) - Syukron, Buyung (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STAIN Jurai Siwo Metro, 2014)
Teachers do not need to be âpreachersâ who continues lecturing and cramming the students with a lot of theories. In this modern era, a child should not be treatedlike a âwastebasketâ which just became a reservoir of knowledge. Learners need tobe treated as a whole and holistic as human learner will absorb the experience as much as possible through the learning process interesting and fun. Therefore, the class needs to be designed as a âmini-societyâ that is able to provide an overview of how the students interact with each other. In other words, the class should be able to become a âmagnetâ that can suck the studentsâ interest and attention of studentsÂ to continue to learn, not as prison that restrains their freedom to think, talk, argue, take the initiative, or interaction.Keywords: Deep dialogue/critical thinking, teaching methood, innovative.